2009
DOI: 10.1099/ijs.0.001693-0
|View full text |Cite
|
Sign up to set email alerts
|

Methylobacterium phyllosphaerae sp. nov., a pink-pigmented, facultative methylotroph from the phyllosphere of rice

Abstract: A pink-pigmented, aerobic, facultatively methylotrophic bacterial strain, CBMB27 T , isolated from leaf tissues of rice (Oryza sativa L. 'Dong-Jin'), was analysed using a polyphasic taxonomic approach. Comparative 16S rRNA gene sequence-based phylogenetic analysis placed the strain in a clade with the species Methylobacterium oryzae, Methylobacterium fujisawaense and Methylobacterium mesophilicum; strain CBMB27 T showed sequence similarities of 98.3, 98.5 and 97.3 %, respectively, to the type strains of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 47 publications
2
40
1
8
Order By: Relevance
“…Although in low occurrence, Methylobacterium was found in the tissue of sugarcane, and this result corroborates with previous studies that reported this genus associated with sugarcane (Madhaiyan et al, 2006), rice (Madhaiyan et al, 2009), sunflower, corn, and soybean (Raja et al, 2008). These bacteria promote the plant growth through several mechanisms, such as using methanol as carbon source, production of hormones, auxins, and cytokinins (Raja et al, 2008).…”
Section: Resultssupporting
confidence: 90%
“…Although in low occurrence, Methylobacterium was found in the tissue of sugarcane, and this result corroborates with previous studies that reported this genus associated with sugarcane (Madhaiyan et al, 2006), rice (Madhaiyan et al, 2009), sunflower, corn, and soybean (Raja et al, 2008). These bacteria promote the plant growth through several mechanisms, such as using methanol as carbon source, production of hormones, auxins, and cytokinins (Raja et al, 2008).…”
Section: Resultssupporting
confidence: 90%
“…So far, a number of bacterial isolates from the rice phyllosphere have been characterized (Elbeltagy et al, 2000;Madhaiyan et al, 2007Madhaiyan et al, , 2009Mano et al, 2007) and potential beneficial interactions of phyllosphere bacteria with rice plants, such as plant growth promotion, for example, by bacterial nitrogen fixation or plant hormone production, and protection against pathogens have been studied (Madhaiyan et al, 2004;Maliti et al, 2005;De Costa et al, 2008;Yang et al, 2008;Chinnadurai et al, 2009;Pedraza et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The 16S rDNA gene sequences were amplified with universal primers 27F (5ʹ-agagtttgatcatggctcag-3ʹ) and 1492R (5ʹ-tacggttaccttgttacgactt-3ʹ) [35]. The PCR products were then analysed via agarose gel electrophoresis.…”
Section: Isolation and Identification Of Bacterium C Israelensis Ld532mentioning
confidence: 99%